A Future Without Hate or Need: The Promise of the Jewish Left in Canada - Reiter, Ester (Between the Lines, 2016)
Driven from their homes in Russia, Poland, and Romania by pogroms and poverty, many Jews who came to Canada in the wave of immigration after the 1905 Russian revolution were committed radicals. A Future Without Hate or Need brings to life the rich and multi-layered lives of a dissident political community, their shared experiences and community-building cultural projects, as they attempted to weave together their ethnic particularity—their identity as Jews—with their internationalist class politics.–Publisher's description
OCLC: 957507446
Keywords: 1900-1999; Canada; Canada Emigration and immigration History 20th century; Canada Émigration et immigration Histoire 20e siècle; Communism and Judaism; Communism and Judaism Canada History 20th century; Communisme et judaïsme Canada Histoire 20e siècle; History; Jewish socialists Canada; Jews; Jews Canada History; Jews Canada History 20th century; Jews Canada Identity; Jews Canada Politics and government; Jews Canada Social life and customs; Jews Identity; Jews Political activity Canada; Jews Politics and government; Jews Social life and customs; Judaism and politics; Judaism and politics Canada History 20th century; Judaïsme et politique Canada Histoire 20e siècle; Juifs Canada Histoire; Juifs Canada Histoire 20e siècle; Juifs Canada Identité; Juifs Canada Mœurs et coutumes; Juifs Canada Politique et gouvernement; Socialism and Judaism; Socialism and Judaism Canada History 20th century; Socialisme et judaïsme Canada Histoire 20e siècle